The temporal dynamics of dissociation: protocol for an ecological momentary assessment and laboratory study in a transdiagnostic sample - Johannes B. Heekerens; James J. Gross; Sylvia D. Kreibig; Katja Wingenfeld; Stefan Roepke (BMC Psychology, 2023)
Abstract Background Dissociation is a ubiquitous clinical phenomenon. Dissociative disorders (DD) are primarily characterized by dissociation, and dissociative states are also a criterion for borderline personality disorder (BPD) and the dissociative subtype of post-traumatic stress disorder (PTSD). Dissociative reactions (e.g., depersonalization/derealization or gaps in awareness/memory) across diagnostic categories are believed to be affect contingent and theorized to serve affect regulation functions. What is not clear, however, is how self-reported affect and physiological reactivity unfold within dissociative episodes. To address this issue, the present project aims to investigate the hypothesis (1) whether self-reported distress (as indicated by arousal, e.g., feeling tense/agitated, and/or valence, e.g., feeling discontent/unwell) and physiological reactivity increase before dissociative episodes and (2) whether self-reported distress and physiological reactivity decrease during and after dissociative episodes in a transdiagnostic sample of patients with DD, BPD, and/or PTSD. Methods We will use a smartphone application to assess affect and dissociation 12 times per day over the course of one week in everyday life. During this time, heart and respiratory rates will be remotely monitored. Afterwards, participants will report affect and dissociative states eight times in the laboratory before, during, and after the Trier Social Stress Test. During the laboratory task, we will continuously record heart rate, electrodermal activity, and respiratory rate, as well as measure blood pressure and take salivary samples to determine cortisol levels. Our hypotheses will be tested using multilevel structural equation models. Power analyses determined a sample size of 85. Discussion The project will test key predictions of a transdiagnostic model of dissociation based on the idea that dissociative reactions are affect contingent and serve affect regulation functions. This project will not include non-clinical control participants. In addition, the assessment of dissociation is limited to pathological phenomena.